ANALISIS SEKTOR-SEKTOR UNGGULAN PEREKONOMIAN DI KABUPATEN HULU SUNGAI TENGAH - SITI ZAINAB (PPJP Universitas Lambung Mangkurat, 2018)
A country or territory will not develop if it is not supported by economic growth. Economic growth is one of the indicators to measure the success of development. The purpose of this research is to know the superior sectors of economy in Hulu Sungai Tengah Regency, so that it can assist in development and priority of government in development. To answer the problem, then used some method of data analysis that is: Location Quotient Analysis (LQ) and Shift-Share Analysis. The data used in this research is secondary data in the value of Gross Regional Domestic Product (GRDP) of Hulu Sungai Tengah Regency at constant prices year 2012-2016. The result of the research based on Location Quotient (LQ) analysis shows that the main base sector in Hulu Sungai Tengah is the sector of accommodation and drinking (1.97%), government administration, defense and compulsory social security (1.87%), agriculture, forestry and fisheries (1.82%), education services (1.72%), real estate (1.58%), waste water management and recycling (1.32%), information and communications (1.32 %), procurement of electricity and gas (1.31%), other services (1.27%), large and retail trade and auto and motorcycle repairs (1.21%), construction (1.19%), (1.19%), health services and social activities (1.11%). The result of Shift-Share analysis shows that there has been a shift of economic structure from the primary sector to the secondary sector.Keywords: Commodity Sector, Location Quotient, Shift Share